Analisis Variasi Nilai Time Repetition (TR) dan Time Inversion (TI) terhadap Informasi Anatomi Sekuens Turbo Inversion Recovery Magnitude (TIRM) MRI Wrist Joint Dengan Menggunakan MRI 0,3 Tesla - Slamet Fujianto; Sugiyanto Sugiyanto; Mohamad Irwan Katili (Jurnal Imejing Diagnostik (JImeD), 2016)
Backgroud: The Turbo Inversion Recovery Magnitude (TIRM) pulse sequence is used to examine wrist joint, especially in the coronal plane. Main parameters of inversion recovery pulse sequence are time repetition (TR), time echo (TE) and time inversion (TI). This study aims to analyze the variation of time repetition (TR) and time inversion (TI) on anatomical information using TIRM pulse sequence on wrist joint MR imaging with 0,3 tesla.Methods: This study was a quantitave experimental study with a linear regression test. This study was conducted in Radiology Department of Banyumas hospital using twenty serial images from only one patient with 10 variation of TR (3000 ms, 3200ms, 3400 ms, 3600 ms, 3800 ms, 4000 ms, 4200 ms, 4400 ms, 4600 ms, 4800 ms) and 10 variation of TI (70 ms, 75 ms, 80 ms, 85 ms, 90 ms, 95 ms, 100 ms, 105 ms, 110 ms, 115 ms). Image assessed by only one respondent.Results: There was no significant influence of variation of TR and TI on anatomical information. Significant number was 0,240 which is bigger than p value (0,05). TR and TI variation affected just only 15,5% to anatomical information, 84,5% was influenced by other variables that unconfirmed in this study.Conclusion: There was differences of anatomical information in MRI wrist joint sequence coronal T2WI-FSE fat suppression between SPIR and SPAIR with a significance level of p value 0.001 (p 0.05). SPAIR is the method which is clearer to show the anatomical information of wrist joint.